THE EFFECT OF SOAKING TIME USING Vinegar (CH3COOH) ON THE ORGANOLEPTIC QUALITY OF LOKAN (Geloina erosa) - Shafa Tasya Rinanda; Mirna Ilza; Mery Sukmiwati (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
ABSTRACT The quality of the shellfish used as raw material in processing greatly affects the smoothness of the processing process, and determines the quality of the resulting product. This study aimed to determine the organoleptic quality of lokan (Geloina erosa) soaked in vinegar (CH3CHOOH). The treatment factor was lokan soaked with a long soaking time of 60 minutes, 90 minutes and 120 minutes using 25% vinegar. Organoleptic data were analyzed by ANOVA and Turkey’s HSD test. The results obtained from the 3 test parameters obtained the highest organoleptic (appearance) value (7,27); lowest (6,63); the highest organoleptic (odor) value (5,49); lowest (5,27); the highest organoleptic (texture) value (7,44); lowest (6,24). That the vinegar immersion had an effect on the organoleptic quality of lokan.Keywords: Lokan, vinegar, organoleptic